Neonatal Hypoglycemia and Brain Vulnerability - De Angelis, Laura Costanza; Brigati, Giorgia; Polleri, Giulia; Malova, Mariya; Parodi, Alessandro; Minghetti, Diego; Rossi, Andrea; Massirio, Paolo; Traggiai, Cristina; Maghnie, Mohamad; Ramenghi, Luca Antonio (Frontiers in Endocrinology, 2021)
Neonatal hypoglycemia is a common condition. A transient reduction in blood glucose values is part of a transitional metabolic adaptation following birth, which resolves within the first 48 to 72 hours of life. In addition, several factors may interfere with glucose homeostasis, especially in case of limited metabolic stores or increased energy expenditure. Although the effect of mild transient asymptomatic hypoglycemia on brain development remains unclear, a correlation between severe and prolonged hypoglycemia and cerebral damage has been proven. A selective vulnerability of some brain regions to hypoglycemia including the second and the and third superficial layers of the cerebral cortex, the dentate gyrus, the subiculum, the CA1 regions in the hippocampus, and the caudate – putamen nuclei has been observed. Several mechanisms contribute to neuronal damage during hypoglycemia. Neuronal depolarization induced by hypoglycemia leads to an elevated release of glutamate and aspartate, thus promoting excitotoxicity, and to an increased release of zinc to the extracellular space, causing the extensive activation of poly ADP-ribose polymerase-1 which promotes neuronal death. In this review we discuss the cerebral glucose homeostasis, the mechanisms of brain injury following neonatal hypoglycemia and the possible treatment strategies to reduce its occurrence.